The implementation of a multi-bus supported ECU calibration system based on XCP - Ren Yinhang (Dianzi Jishu Yingyong, 2018)
Most calibration systems developed in our country for now are based on the CAN calibration protocol(CCP), which is specially designed for the CAN bus, and thus has poor compatibility and expansibility for other buses. However, the protocol layer of the universal measurement and calibration protocol(XCP) is independent from any specific physical transport layer. Based on that, a multi-bus supported ECU calibration system is implemented, which is in accordance with the widely accepted industry norms of measurement, calibration and diagnostic system made by association for standardization of automation and measuring system(ASAM-MCD). The XCP driver is developed in both master and slave nodes, and XCP transport layers for CAN and FlexRay are designed respectively on the basis of the same protocol layer, so that the system is suitable for both the mature CAN bus and the promising FlexRay bus. The system is tested through measurement and calibration experiments, and the results demonstrate that it satisfies the requirements well.